Interaction between AhR and HIF-1 signaling pathways mediated by ARNT/HIF-1β - Mengdi Zhang; Yuxia Hu; Fan Yang; Jingwen Zhang; Jianxin Zhang; Wanjia Yu; Minjie Wang; Xiaoli Lv; Jun Li; Tuya Bai; Fuhou Chang (BMC, 2022)
Abstract Background The main causes of lung cancer are smoking, environmental pollution and genetic susceptibility. It is an indisputable fact that PAHs are related to lung cancer, and benzo(a) pyrene is a representative of PAHs. The purpose of the current investigation was to investigate the interaction between AhR and HIF-1 signaling pathways in A549 cells, which provide some experimental basis for scientists to find drugs that block AhR and HIF-1 signaling pathway to prevent and treat cancer. Methods This project adopts the CYP1A1 signaling pathways and the expression of CYP1B1 is expressed as a measure of AhR strength index. The expression of VEGF and CAIX volume as a measure of the strength of the signal path HIF-1 indicators. Through the construction of plasmid vector, fluorescence resonance energy transfer, real-time quantitative PCR, western blotting and immunoprecipitation, the interaction between AhR signaling pathway and HIF-1 signaling pathway was observed. Results BaP can enhance the binding ability of HIF-1α protein to HIF-1β/ARNT in a dose-dependent manner without CoCl2. However, the binding ability of AhR protein to HIF-1β/ARNT is inhibited by HIF-1α signaling pathway in a dose-dependent manner with CoCl2. Conclusion It is shown that activation of the AhR signaling pathway does not inhibit the HIF-1α signaling pathway, but activation of the HIF-1α signaling pathway inhibits the AhR signaling pathway.